Chrysin or mannitol for treatment of acute kidney injury: Evidence for pharmacokinetic interaction - Heba M. I. Abdallah, Sally A. El Awdan, Salma A. El-Marasy, Omar A. Ahmed-Farid, Azza Hassan (Journal of Applied Pharmaceutical Science, 2021)
Acute kidney injury (AKI) is a heterogeneous disorder that is associated with high percent morbidity and mortality especially in hospitalized patients. Seeking new drugs that have pleiotropic effects on multiple pathologic pathways to treat AKI is a demand. The study aims to investigate and compare the protective effects of chrysin, mannitol, and their combination on an ischemia-reperfusion (I/R) injury rat model. Rats were allocated into 5 groups: sham-operated group, I/R control group, and three groups administered with chrysin (50 mg/kg, p.o.), mannitol (0.75 ml/100 g bw of 20% mannitol, i.p.), and chrysin + mannitol, respectively. Biochemical parameters were measured. Histological examination, immunohistochemical analysis of apoptotic markers (caspase-3 and Bax), and pharmacokinetic (PK) study were also performed. Chrysin improved kidney injury indicators, malondialdehyde (MDA), reduced glutathione, inflammatory mediators (prostaglandin E2 and cyclooxygenase-2), and interleukin 1-beta that were deteriorated after I/R injury. It also protected against increased renal damage score and expression of caspase-3 and Bax. The renoprotective effect of chrysin was comparable to mannitol; however, the combination of both drugs resulted in weak protection against renal injury and showed a decrease in PK parameters Cmax and area under the plasma concentration-time curve as compared to chrysin alone. Both chrysin and mannitol protect against AKI after ischemia-reperfusion via multitarget mechanisms. The combination resulted in a PK interaction.
Keywords: ischemia-reperfusion, chrysin, mannitol, pharmacokinetics, rats